Development of Interactive E-Modules as a Learning Media to Train Visual-Spatial Intelligence on Intermolecular Force Materials - Pratamadita, Aulia; Dwiningsih, Kusumawati (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2022)
This research aims to determine the feasibility of the interactive e-module from its validity, effectiveness, and practicality as a learning media for high school students to train visual-spatial intelligence on intermolecular forces materials. The type of this research is Research and Development (R&D) with the ADDIE development model. There are five (5) stages at the ADDIE model, namely: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. The instruments used in the interactive e-module validation process were content and construct validation sheets, pretest and posttest sheets for effectiveness, and student response questionnaires for its practicality. This researchsâ€™ data were analyzed descriptively quantitatively. The results of the interactive e-module validation obtained a percentage of 90.0% for content validation and a percentage of 90.5% for construct validation, both of which belonged to the very valid category. The effectiveness of the interactive e-module also met the classical completeness criteria, which is 80.0% in the intermolecular force material and 85.0% in the visual-spatial. The T-test results also showed a significant difference between the average pretest and posttest indicated by the sig. 2-tailed value of 0.00 < 0.05 both in terms of intermolecular forces and visual-spatial. In addition, interactive e-modules were also said to be practical to use based on student responses which showed a score of 100% on the content aspect, 99.2% on the linguistic aspect, 97.1% on the usability aspect, and 100% on the presentation aspect. All of them were in the â€œVery goodâ€ category. From these results, it can be concluded that the interactive e-module to train students' visual-spatial intelligence on the material of intermolecular forces is feasible to use in terms of validity, effectiveness, and practicality.